58 Use of Abdominal Wall or Sucutaneous Drain to Reduce the Risk of Surgical Site Infections. (4th May 2021) - Mistry, H; Woolner, B; John, A
Abstract: Introduction: Open abdominal surgery confers potentially greater risk of surgical site infections, and local evidence suggests use of drains can reduce this. Our objectives were: Assessing local rates and risk factors of infections and if use of drains can reduce the rates of infections. Method: Retrospectively looking from 01/01/2018 to 31/12/2018, at patients following laparotomy or open cholecystectomy. Data collection on demographics, smoking/alcohol status, heart, respiratory or renal disease or diabetes, steroid use and CEPOD status, as well as use of drain and the outcome of infection using inpatient and online patient records. Results: 84 patients included, 25 had drains inserted. There were 13 documented cases of surgical site infection, all of whom had no drain post-op. Other parameters shown to be most prevalent in the patients with a surgical site infection include being current/ex-smoker (8/13), having heart disease (9/13), and elective procedures. Conclusions: Aiming to reduce the risk of surgical site infections can improve morbidity and potentially mortality outcomes. Our audit data showed that there appears to be a benefit of inserting intra-abdominal or subcutaneous drains. We will create a standard operating procedure of all patient to receive drains post-op and then re-audit to assess the impact this has on infection rates.